Social Consumer Relation Management Using Social Media as a Marketing Scheme in University - Ali Ibrahim; Iredho Fani Reza; Mansyur Abdul Hamid; Hadiansyah Ma'sum; Heliza Rahmania Hatta; Aryo De Wibowo; Rahmat Izwan Heroza (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2023)
Social media or called as ‘socmed’ is an online media that is frequently used by humans to improve in activities, which include promoting study programs of university. Most universities require a marketing scheme to promote certain study programs by using socmed. This study aims to investigate marketing strategies of universities using social costumer relation management (SCRM) and socmed. This is a qualitative study with a narrative model design. This study included about 2000 students from universities in South Sumatra, Lampung, Bengkulu, and Bangka Belitung, Indonesia. The samples were collected by proportional random sampling approach to attain the number of informants and data were collected through online interview questionnaire. Furthermore, the data were analyzed using coding approaches (open, axial, and selective coding) and value stream analysis. The findings revealed that SCRM can be an alternative marketing scheme for universities that utilize socmed to disseminate information owing to access easiness, complete and updated information, and attractive appearance.